2021
DOI: 10.1038/s41598-021-88640-7
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic evaluation of carcinogenesis in endometrial cancer

Abstract: Carcinogenesis is a multifaceted process of cancer formation. The transformation of normal cells into cancerous ones may be difficult to determine at a very early stage. Therefore, methods enabling identification of initial changes caused by cancer require novel approaches. Although physical spectroscopic methods such as FT-Raman and Fourier Transform InfraRed (FTIR) are used to detect chemical changes in cancer tissues, their potential has not been investigated with respect to carcinogenesis. The study aimed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…Positive peaks suggested positive correlations, while negative peaks indicated negative correlations, and zero represented no effect [ 39 ]. The regression vectors showed the discriminating region was dominated in 1710–1510 cm −1 by the bands centered at 1643, 1628, 1598, 1575 and 1515 cm −1 , characteristic of C=O stretching vibrations in Amide I, the β-sheet structure, the N-H bend, the C–C aromatic ring, and the C=C stretch of aromatic compounds, respectively [ 5 , 53 , 54 , 55 , 56 ]. Furthermore, amide bands and aromatic rings in the profiles of the regression vector for all four models were consistently important.…”
Section: Resultsmentioning
confidence: 99%
“…Positive peaks suggested positive correlations, while negative peaks indicated negative correlations, and zero represented no effect [ 39 ]. The regression vectors showed the discriminating region was dominated in 1710–1510 cm −1 by the bands centered at 1643, 1628, 1598, 1575 and 1515 cm −1 , characteristic of C=O stretching vibrations in Amide I, the β-sheet structure, the N-H bend, the C–C aromatic ring, and the C=C stretch of aromatic compounds, respectively [ 5 , 53 , 54 , 55 , 56 ]. Furthermore, amide bands and aromatic rings in the profiles of the regression vector for all four models were consistently important.…”
Section: Resultsmentioning
confidence: 99%
“…More recently, Depciuch et al [9] identified the chemical changes that occur during the carcinogenesis process in endometrial tissues with both Raman and FtIR spectroscopy and reported classification accuracy ranging between 62.71 and 96.61%; the research group further combined Raman and FtIR spectroscopy to differentiate endometrial cancer, atypical hyperplasia and controls [10]. Alterations in nucleic acid, Amide I, lipids and collagen were seen in the Raman spectra, while changes in carbohydrates and amide vibrations were shown in the FtIR spectra.…”
Section: Endometrial Cancer Diagnosismentioning
confidence: 97%
“…Increasingly more data are emerging in support of the role of vibrational biospectroscopy techniques as cancer diagnostic and screening tools [7,8], as well as the potential role in the assessment of endometrial pathology [9,10]. It is relevant, therefore, to highlight the status quo of the progress made to date in applying vibrational biospectrscopy techniques to EC.…”
Section: Introductionmentioning
confidence: 99%
“…3a-3c. 41,42,58,59 Wavenumber (cm reported that CAFs derived from EC patients with increasing BMI are also less responsive to the hormonal treatment, medroxyprogesterone acetate, with a perturbed metabolic phenotype associated with high expression of CD36 and lipid droplet formation. 78 Multiple metabolomic analyses have also demonstrated the diagnostic role of saturated fatty acid as a potential noninvasive biomarker for the detection and characterization of gynecological cancers including ovarian, 79 endometrial, 80 and breast cancer.…”
Section: Ratiometric Analysismentioning
confidence: 99%